Efektivitas Pengambilan Keputusan Kepala Sekolah SMK di Yogyakarta - Didi Supriadi; Rejokirono Rejokirono (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
It is important for the main decision-making of vocational schools to maintain managerial effectiveness. To order to achieve educational goals, vocational school administrators can choose a decision-making method that fits the problem facing them. The aim of this study was to analyze the effectiveness of vocational school pricincipal’s decision making. This research is a quantitative descriptive study with a questionnaire as a research instrument. The research sample is the headmaster of a vocational school in the Special Region of Yogyakarta. The methodology used in this study for analyzing data is descriptive analysis. The results showed that in decision-making the SMK headmaster was quite successful. This can be seen from the systematic and organized decision-making, re-evaluating as new information is available, assessing the effects of the decision, and communicating the decision basis effectively.Keywords: effectiveness of decision, vocational school, principal decision making